"Breivik is my Hero": the Dystopian World of Extreme Right Youth on the Internet. (September 2014) - Turner‐Graham, Emily
<x xml:space="preserve">Abstract</x> The extreme right is currently on the rise throughout Europe, making use of the Continent's economic and social problems to bolster its cause. It is also making increasing use of the Internet to spread its message and build a virtual world that it hopes will one day be reflected in reality. Until now the bulk of research into the extreme right's use of the Internet has focused on the online activities of political parties and organised groups. But the horrific acts of the Norwegian terrorist, counterjihadist and lone wolf Anders Behring Breivik, and his promotion of those acts and the ideology behind them by way of the Internet, has provoked an array of microblogs — that is, cutting‐edge web presences made up of provocative short sentences, single images or video links. They idolise Breivik and reveal the potent use the extreme right is making of alternative media. The creators of these pro‐Breivik counterjihadist sites are often young people well‐versed in the use of the multi‐faceted new media and as such they are able to create an appealing vision of their brave new world. They often work independently, producing a virtual worldview from the seclusion and relative anonymity of home computers. They are creating virtual places of congregation, community and validation for vulnerable young people in search of identity, purpose and meaning. In doing so, a new range of radical voices is being cultivated and added to current extreme right discourse. This paper will examine the extreme right's use of the Internet and the specific use made by its pro‐Breivik, counterjihadist voices — the new voices of the extreme right.